An Analysis of Paragraph Writing Abilities of English Department Students UNM - Indrawaty Asfah (Universitas Negeri Makassar, 2019)
Studies on the errors of linguistic elements in students’ writings have been carried out. Students learning English as a Foreign Language from various universities seem tomake the time same type of errors, for example in aspects of tenses, verb forms, perpositions, subject-verb agreement, word order, and passive contrainst (Rahman et al. 2016; Murrow, 2004; Rahman, 1994; & Rahman & Rasyid). This study is expected to find the weaknessess of students of English Department, Faculty of Languages and Literature in terms of paragraph writing. In particular, this research examined the ability of students to write or develop paragraphsin terms of unity, coherence, and development aspects. The findings of this study will be useful for instructors/lecturers of Writing couses especially in developing syllabus and effective writing exercises.